FACTORS INFLUENCING THE READINESS TO PAY FOR FLOOD MOTOR INSURANCE AMONG PRIVATE VEHICLE OWNERS IN KEDAH, MALAYSIA - Tan, Xue Jia; Lai , Chuah; Ng, Ka Cien Angel; Lee, Zi Yu; Kong , Keong Leong; Osman, Nor Hasni; Rashed, Muhammad Ali Imran Mohamed; Elias, Ezanee Mohamed; Oloruntobi, Olakunle; Othman, Mohammad Khairuddin (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
Frequent flooding poses substantial risks to private motor vehicle owners in Malaysia, resulting in significant financial losses and mobility disruption. Despite repeated flood events, the uptake of flood motor insurance remains low as flood protection was offered only through an optional special perils’ extension. This study examined the influence of financial factors (financial capacity and perceived affordability of insurance premiums), flood awareness, geographical exposure, trust in insurance providers and past flood experience on readiness to pay (RTP) for flood motor insurance among private vehicle owners in Kedah, Malaysia. The study was grounded in Protection Motivation Theory, which explains protective financial behaviour through threat appraisal and coping appraisal processes. Data from 384 respondents were collected using cluster sampling and analysed with multiple linear regression in SPSS version 27. The findings revealed that financial factors, flood awareness, geographical exposure and trust significantly influenced RTP, whereas past flood experience was not significant. Financial factors emerged as the strongest predictor of RTP (β = 0.429, p < 0.001), followed by trust (β = 0.257, p < 0.001) and flood awareness (β = 0.165, p < 0.001), highlighting the importance of financial affordability and institutional trust in shaping insurance payment decisions. The results suggested that coping appraisal evaluations outweigh experiential exposure in influencing insurance adoption. This study contributed to climate-related insurance literature in developing economies by identifying affordability and institutional trust as primary determinants of flood insurance payment readiness. The findings provided implications for insurers and policymakers to design affordable, transparent and risk-responsive flood motor insurance schemes that enhance household financial resilience in flood-prone regions of Malaysia. Future research might extend this analysis to other states, adopt longitudinal or mixed-method approaches and further examine how experience interacts with financial and institutional factors in shaping insurance behavior.